Spatial memory in rufous hummingbirds: memory for rewarded and non-rewarded sites - HURLY, ANDREW T. (Animal behaviour, 1996)
The foraging ecology of rufous hummingbirds, Selasphorus rufus, suggests that this species may have good spatial memory capabilities. Six adult male hummingbirds were tested in a one-trial learning experiment in the field. Subjects searched for a single sucrose reward among four identical artificial flowers (Search Phase). Following a retention interval, subjects returned to locate the reward again (Return Phase). Performance during the Search Phase was no better than expected by chance, indicating that the hummingbirds could not detect the sucrose through intrinsic cues (e.g. odour). During the Return Phase, subjects performed significantly better than chance and could have done so only by remembering the spatial location of rewarded flowers. In addition, subjects avoided revisiting non-rewarded flowers, suggesting memory for these locations as well. Finally, information about rewarded and non-rewarded locations was combined to direct sampling behaviour towards flowers the birds had not yet encountered.